A Comprehensive Review on In Silico-predicted Potential Phytochemicals against SARS-CoV-2: Food for Thought for Researchers - Pathak, Shilpi; Agrawal, Neetu; Goyal, Ahsas (Letters in Organic Chemistry, 2022)
The novel coronavirus disease (COVID-19) emerged in December 2019. It is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and is still existent all over the world. Researchers worldwide are continuously conducting in silico studies or virtual screening on various phytochemicals and reporting potential candidates that can be developed against COVID-19 after in vitro and in vivo validation. Antiviral effects of several phytochemicals have been demonstrated against different kinds of coronavirus, including SARS-CoV. Using drug repurposing techniques, a number of phytochemicals have shown substantial antiviral efficacy against COVID 19. This article reviews the efficacy of lead phytochemicals in computational studies on different important targets of SARS-CoV-2 like main protease, ACE-2, papain-like protease, spike protein, nsp-1, nsp-15, RdRp, MTase, helicase, cathepsin, TMPRSS-2. This review discusses potential application of these phytochemicals, which can guide medicinal chemists to choose phytochemicals to proceed with further in vitro and in vivo testing for SARS-CoV-2, which may eventually lead to an effective therapeutic agent and thus can be used to control the current ongoing pandemic.
Keywords: In silico